99.1k views
5 votes
Solve the equation.

4 – t = 3(t – 1) – 5
A. 3
B. 6
C. no solution
D. identity

User Voldy
by
4.4k points

2 Answers

3 votes

Answer is "A".

My reasoning is, I did this in class.

User Martin Spamer
by
4.5k points
3 votes

Answer:

A

Explanation:

Given

4 - t = 3(t - 1) - 5 ← distribute and simplify right side

4 - t = 3t - 3 - 5

4 - t = 3t - 8 ( subtract 4 from both sides )

- t = 3t - 12 ( subtract 3t from both sides )

- 4t = - 12 ( divide both sides by - 4 )

t = 3 → A

User Ed Bayiates
by
4.9k points